Low Head Pico-Hydro: A Robust Rural Renewable Energy Technology for Remote Rural Areas - Gautam, Biraj (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The rural electrification is the most needed pill for equitable economic and environmental development of Nepal. However, it comes with great challenges. The cost involved for grid extension, availability of power in grid and pre-condition required for alternate energy options for affordable rural energy supply significantly hinders the process of rural electrification. The low-head Pico-hydro is a promising technology which has positioned itself in a special niche of renewable energy technologies and is very important to address the problems Nepal is currently facing. DOI: http://dx.doi.org/10.3126/hn.v11i0.7166 Hydro Nepal Vol.11 2011 pp.64-66